Three- hop Distributed Routing Protocol for Hybrid Network - jacob, Judith; koyakutty, Shinu (IJRDO -Journal of Computer Science Engineering, 2015)
Hybrid wireless networks combining theadvantages of both mobile ad-hoc networks and infrastructurewireless networks .Network simply combine ad-hoctransmission mode with cellular transmission mode.Distributed Three-hop Routing protocol (DTR) for hybridwireless networks take full advantage of the widespread basestations, DTR divides a message data stream into segmentsand transmits the segments in a distributed manner.Furthermore, sending segments to a number of base stationssimultaneously increases throughput and makes full use ofwidespread base stations. DTR significantly reduces overheaddue to short path lengths and the elimination of routediscovery and maintenance. DTR also has a congestioncontrol algorithm to avoid base stations overload. DTR incomparison with other routing protocols in terms ofthroughput capacity, scalability and mobility resilience. Datasplitting based on Chinese remainder theorem will reduce dataloss and lost data can be recollected.